The Effect of Bidara (Ziziphus spina-christi (L.)) Leaf Extract Adding on Physicochemical and Sensory Properties of Milk Candy - Nurfebriana, Putri Selvia; Lestari, Suci Puji; Purnamasari, Fitri (Faculty of Animal Science Universitas Brawijaya, 2026)
Milk candy or milk caramel is a dairy product with the main ingredients of milk, sugar and additional ingredients of margarine and jelly. The addition of leaf extract of bidara (Ziziphus spina-christi (L.)) using Microwave Assisted Extraction (MAE) is expected to control the browning reaction and increase the nutritional value of milk candy. The purpose of this study was to determine the addition of bidara leaf extract on physicochemical and sensory properties of milk candy. The method used was laboratory experiment by using Completely Randomized Design (CRD) using four treatments and three replications were without addition or control (P0), 1% bidara leaf extract (P1), 2% bidara leaf extract (P2) and 3% bidara leaf extract (P3). Data were analyzed by analysis of variance (ANOVA) and continued with Duncan's Multiple Range Test. The results of bidara leaf extract addition to milk candy showed highly significant effect (p < 0.01) for moisture content, total acid, color (L* a* b*) and sensory test (color, texture and taste) but have no significant effect (p > 0.05) for reducing sugar content and color index. The addition of leaf extract of bidara improved physicochemical and sensory properties of milk candy.